Analysis of Bakery Business Revenue in The Home Industry of 257 Roti Bandung in Palu City - Adriansah, A.; Yunus, Rita (Golden Ratio of Data in Summary, 2024)
The industry "Home Production 257 Roti Bandung" is one of the businesses that produces bread, this industry is located on Jalan Jl. Basuki Rahmat. Lorong Cendana 2, Kel. North Tatura District. South Palu. Home Production 257 Roti Bandung is a home industry that produces fresh and baked bread. This research aims to analyze the income earned by the Home Production Business 257 Roti Bandung in South Palu City. The determination of respondents in this research was carried out purposively, the respondents chosen were leaders, the data used in this research consisted of primary data and secondary data. As a result of the analysis that has been carried out, it is known that the income of the 257 Roti Bandung Home Production Industry in producing bread is IDR.66.360.667/ month, with receipts of Rp. 118.500.000/ month and the total costs incurred are Rp.52.139.333/month.